Pengaruh Word of Mouth (WOM) dan Daya Tarik Wisata terhadap Keputusan Berkunjung Wisatawan ke Wisata Keraton Kasepuhan Kota Cirebon - Galih Azka Ramadhan; Endah Budiastuti; M Annisul Fata (Yayasan Literasi Sains Indonesia, 2024)
This study aims to determine the influence of Word of mouth variables and tourist attractions on the decision to visit tourists to the Kasepuhan Palace in Cirebon City. The research method used is a quantitative method. The number of samples in this study was 94 respondents. The results of this study indicate that: it is known that t count> t table or 4.748> 1.662 and has a significance value smaller than the significance level of 0.05, namely 0.00 <0.05 with a value of 71.7%, then H0 is rejected and Ha is accepted. So it can be concluded that the Word of mouth variable partially has a positive and significant effect on the Decision to Visit. It is known that t count> t table or 4.383> 1.662 and has a significance value smaller than the significance level of 0.05, namely 0.00 <0.05 with a value of 70.8%, then H0 is rejected and Ha is accepted. So it can be concluded that the variable of Tourist Attraction partially has a positive and significant effect on the Decision to Visit. Based on the calculated F value which is greater than the f table, which is 152.346> 3.94, with a determination coefficient value of 76.1%, this means that the indicator that describes the variable word of mouth and tourist attraction has a simultaneous effect on the variable Decision to Visit.